PREFERENSI TENAGA KERJA DALAM MENGIKUTI PROGRAM PERUSAHAAN PENSIUN DINI ATAU PENSIUN UMUR (STUDI KASUS PT. XX KEDIRI) - Eka Putra, Dadang Gedhe (Jurnal Ilmiah Mahasiswa FEB, 2016)
Indonesia produces a mass amount of human resources every year. Resources in form of human labor will enter in either institutions or companies as a worker. Out of various types of companies, one example that uses lots of human labor is tobacco companies. However, due to regulations from government, tobacco companies can't develop and tend to lose their gains. For that reason, companies made an offer for early pension program to the workers with several conditions. In the end, it is known that workers' preference for pension are early pension and age-based pension. It can be explained from the researches that workers' preference on undergoing early pensions are caused by insentives in the form of severance package, getting social security money from Jamsostek or BPJS, and also benefits from working time. Meanwhile, workers' preference on undergoing age-based pension are caused by larger benefit opportunities, for example, workers can keep getting the expected salaries, health insurance, and Feast Day Allowance (THR), and they can receive another intensives like PTO, double fee, and extra fooding.Â Â Keywords: labor, corporations, pension, government, incentives, preferences, opportunities.